Preparation and characterization of SPE column with smart green molecularly imprinted polymers materials for selective determination of S-metolachlor herbicide - Dominika Rapacz; Katarzyna Smolińska-Kempisty; Joanna Wolska (Scientific Reports)
Abstract The presence of traces of herbicides in ground and surface waters can have adverse impacts on humans and the environment. Therefore, developing a highly selective and reusable adsorbent for monitoring water quality has become important. This article describes smart green molecularly imprinted polymers (MIPs) as selective sorbents of S-metolachlor herbicide for solid phase extraction (SPE). Combining the MIP-SPE column with HPLC chromatography provided a quick and accurate method for determining the real concentration of S-metolachlor in water samples. The sorption capacity of the MIP-SPE column was almost twice that of the non-imprinted polymer column for SPE extraction. The bed can be regenerated up to three times before it loses its original sorption properties. A method has been developed whereby 6 ml of water can achieve an average recovery rate of 98% for sorbent. During the selectivity study from multicomponent solution, the calculate imprinting factor for MIPs was calculated to be 10, while MIPs sorb S-metolachlor 10 times better than atrazine, 12 times better than fenoxaprop-P-ethyl and 33 times better than glyphosate. The pseudo-second-order kinetic model was in good agreement with the experimental values obtained.